Damage detection in bridge structures under moving loads with phase trajectory change of multi-type vibration measurements - Zhang, W.; Li, Jun; Hao, Hong; Ma, H. (Academic Press, 2017)
This paper presents a non-model based damage detection approach for bridge structures under moving loads based on the phase trajectory change of multi-type vibration measurements. A brief theoretical background on the vibration of a simply-supported bridge with a crack under moving load is described. The phase trajectories of multi-type dynamic responses are obtained and a damage index is defined as the separated distance between the trajectories of undamaged and damaged structures to indicate the damage location. Numerical studies on a simply-supported beam structure are conducted to investigate the sensitivity and robustness of the proposed approach to accurately identify the damage location. Experimental studies demonstrate that the proposed approach can be used to successfully identify the shear connection failure in a composite bridge model subjected to moving loads.